Serum neurofilament light chain levels as a marker of upper motor neuron degeneration in patients with Amyotrophic Lateral Sclerosis. (18th July 2018) - Gille, B.; De Schaepdryver, M.; Goossens, J.; Dedeene, L.; De Vocht, J.; Oldoni, E.; Goris, A.; Van Den Bosch, L.; Depreitere, B.; Claeys, K. G.; Tournoy, J.; Van Damme, P.; et al.
Abstract : Aims: Amyotrophic lateral sclerosis (ALS) is the most common motor neuron degeneration disease with a diagnostic delay of about 1 year after symptoms onset. In ALS, blood neurofilament light chain (NfL) levels are elevated, but it is not entirely clear what drives this increase and what the diagnostic performance of serum NfL is in terms of predictive values and likelihood ratios. The aims of this study were to further explore the prognostic and diagnostic performances of serum NfL to discriminate between patients with ALS and ALS mimics, and to investigate the relationship between serum NfL with motor neuron degeneration. Methods: The diagnostic performances of serum NfL were based on a cohort of 149 serum samples of patients with ALS, 19 serum samples of patients with a disease mimicking ALS and 82 serum samples of disease control patients. The serum NfL levels were correlated with the number of regions (thoracic, bulbar, upper limb and lower limb) displaying upper and/or lower motor neuron degeneration. The prognostic performances of serum NfL were investigated based on a Cox regression analysis. Results: The associated predictive values and likelihood ratio to discriminate patients with ALS and ALS mimics were established. Serum NfL was associated with motor neuron degeneration driven by upper motor neuron (UMN) degeneration and was independently associated with survival in patients with ALS. Conclusions: Altogether, these findings suggest that elevated serum NfL levels in ALS are driven by UMN degeneration and the disease progression rate and are independently associated with survival at time of diagnosis.